Anytime, anywhere: Understanding random breath testing deployments at the local level - Green, Darren (Journal of criminology, 2024)
The impact of random breath testing (RBT) on alcohol-related traffic crashes has been the subject of numerous studies over the past 30 years. The existing body of research clearly identifies the positive impact of RBT programmes around the world. However, very little is known about when and where RBT is deployed locally to achieve the desired outcomes. By understanding how RBT is being deployed in space and time opportunities may be identified to improve current practices. To start addressing this gap, the current paper characterises the location and timing of RBT within a Queensland Police District. Results identify RBT is more likely to be conducted within specific locations, on particular days and at particular times. These outcomes provide a level of clarity over the operationalisation of RBT, offering opportunities to explore how this strategy could be varied to try and improve road safety outcomes, for example, increasing the diversity of RBT locations or evening out the number of tests conducted each day of the week to increase the perceived certainty of sanctions. The results also have implications for future research. Of interest would be the impact of RBT predictability on perceptions of avoidance. The repeat police presence also provides an opportunity for future research to explore a potential diffusion of benefit, crime reduction. These implications are discussed, within the context of the extant literature, to guide future research aiming to maximise the efficacy and efficiency of RBT programmes.